Novel Inpatient Radiation Oncology Consult Service Model Reduces Hospital Length of Stay. Issue 12 (December 2021) - Xu, Amy J.; Yerramilli, Divya; Cahlon, Oren; Powell, Simon N.; Yang, Jonathan T.; Gomez, Daniel R.
Abstract : Palliative care and radiation therapy have played an expanding role in the management of patients with advanced cancers. Recent advances in our understanding of oligometastatic disease have led to increasing demand for familiarity with ablative techniques. Recognizing the demands of hospitalized patients for rapid access to care, we created an inpatient radiation oncology consult service (IROC) with consolidated expertise in palliative radiation and ablative techniques. In this quality improvement cohort study, we analyzed inpatient radiation oncology consults placed before and after IROC implementation and found that IROC led to increased delivery of specialty care and decreased hospital length of stay (median 8 days v 7 days, P = .005). This difference was most pronounced for patients for whom radiation therapy was indicated (14.5 v 11 days, P = .007). Our institutional experience demonstrates the value of recognizing metastatic disease as a distinct discipline and providing rapid access to palliative treatments for patients with advanced malignancies.